2022
DOI: 10.6007/ijarbss/v12-i1/12046
|View full text |Cite
|
Sign up to set email alerts
|

Trust in Green Advertising: Mediating Role of Environmental Involvement

Abstract: The Covid-19 pandemic has heightened public interest and awareness of the importance of living sustainably while sparked interest in businesses that make "good" use of their green marketing campaign. Indeed, green marketing has gained wide acceptance within the business world as a viable competitive strategy to grab and win customers' attention in the marketplace. This research sought to investigate how the green advertising environmental claims affect consumers' trust in the green advertisement. The mediating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
1
12
0
1
Order By: Relevance
“…Matthes and Wonneberger [56] investigated the generally believed notion that consumers with green values tend to distrust green advertising and found out that, in fact, they perceive greater informational utility of green advertisements, which actually decreases their skepticism. Tee et al [57] confirmed that consumers with deeper concerns on the environmental protection trusted green advertisement more. By taking into account previous research findings, we propose the following: Hypothesis 1 (H1).…”
Section: Receptivity To Green Communicationmentioning
confidence: 96%
“…Matthes and Wonneberger [56] investigated the generally believed notion that consumers with green values tend to distrust green advertising and found out that, in fact, they perceive greater informational utility of green advertisements, which actually decreases their skepticism. Tee et al [57] confirmed that consumers with deeper concerns on the environmental protection trusted green advertisement more. By taking into account previous research findings, we propose the following: Hypothesis 1 (H1).…”
Section: Receptivity To Green Communicationmentioning
confidence: 96%
“…Within the scope of this study the exploration of the mediator variable, trust in sustainable advertising, takes on paramount significance. Bachnik & Nowacki, (2018); Tee et al, (2022) unveiled the pivotal role played by trust in sustainabilityrelated advertising campaigns. They highlighted that the degree of trust often hinges on the campaigns' accuracy in reflecting an organization's genuine commitment to sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their findings illuminate how engaging with sustainability initiatives promoted through advertising can contribute significantly to the process of trust-building. When consumers perceive that the organization actively involves itself in sustainability-related activities and initiatives, trust is nurtured (Tee et al, 2022). This involvement signifies a tangible commitment beyond marketing campaigns, reinforcing the authenticity of the organization's sustainability endeavors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of retirement, utilization of OFS can ease the operation with an interactive planner for retirement and management of retirement financial products or portfolio (Bruggen et al, 2019). Trust is defined by values and beliefs towards another party with ability, integrity and benevolence (Berry & Parasuraman, 2004;Tee et al, 2022b). Trust itself is a very important variable in determining the long-term relationship between business entities and clients.…”
Section: Trust Towards Online Financial Services (Ofs)mentioning
confidence: 99%